Influence Of Competencies Agent’S Of Change On The Success Of Adopting Sustainable Agriculture - Wardatul Chamro; Reksa Nanda Prayoga; Arissaryadin Aris Arissaryadin (UNIVED Press, Dehasen University Bengkulu, 2026)
Purpose : To identify the dominant factors influencing the successful adoption of sustainable agriculture innovations in Besowo Village, Kepung Subdistrict, Kediri Regency. Methodology : A quantitative approach was used, based on descriptive methods. The research respondents were horticultural farmers in the study area who were members of three farmer groups, namely Tani Mulo, Mekar Sari, and Mawar Indah, with a total sample size of 76 people. Data were collected using a questionnaire and analyzed using multiple linear regression with independent variables including technical competence (X1), communication (X2), and motivation (X3), and the dependent variable being the level of innovation adoption (Y). Results : The competencies of change agents simultaneously influence the level of innovation adoption, with an F-value of and a significance level of 0.007 < 0.05. However, when analyzed partially, the variables of technical competence and motivation did not have a significant effect, whereas communication competence had a significant effect on the adoption of environmentally friendly innovations. This explains that the ability of change agents to communicate materials and practices has a greater influence on farmers’ adoption of environmentally friendly agricultural innovations. Findings : These findings can assist field extension officers in appropriately enhancing their competencies to promote increased and sustainable adoption of environmentally friendly agriculture. Originality : This study was specifically conducted in Besowo Village, Kepung Subdistrict, Kediri Regency, and the sample was drawn directly from local horticultural farmers. Conclusion : Simultaneously, the competencies of extension workers as agents of change—namely technical, Communication, and motivation influence farmers in adopting environmentally friendly agricultural innovations. However, partially, only communication competence has a significant effect. Type of Paper : Research Article.